Theories of Business Cycle in Terms of Study of Control - Leszek RYDZAK; Monika STOMA; Agnieszka DUDZIAK (Communications of International Proceedings, 2021)
A set of theories of business cycle, developed on economic basis, have been presented in this paper. The systemic analysis that aims at developing such a theory from the perspective of cybernetics, which is the study of control, has also been presented. This analysis was based on the possessions of the polish cybernetic school, the leader of which , Marian Mazur, was the creator of the qualitative theory of information. In the course of the analysis, all transactions made int he market were aggregately divided into those that are controlled by an external system referred to as an Organizer and those that are not subject to any control by any external system.  The conceptual and specific set of notions for the polish cybernetic school was used for this paper purposes, but the conceptual framework used in it has been precisely defined. As a result of the carried out analysis, it has been stated that the reason of periodicity occurring in the economy is the organizer’s excessive influence on the system which is controlled by him, as a consequence, it leads to exhaustion of the energetic system and loss of  the organizer’s control possibilities.
Keywords: Business cycle; cybernetics; market; systems